2012
DOI: 10.1016/j.amepre.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Walking Distance by Trip Purpose and Population Subgroups

Abstract: Background Walking distance is an important concept in the fields of transportation and public health. A distance of 0.25 miles is often used as an acceptable walking distance in U.S. research studies. Overall, research on the distance and duration of walking trips for different purposes and across different population groups remains limited. Purpose This study examines the prevalence of walking and distances and durations of walking trips for different purposes among U.S. residents. Methods The distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
216
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(230 citation statements)
references
References 33 publications
6
216
1
7
Order By: Relevance
“…Park neighborhoods were defined by a one-half-mile buffer around the park, about the distance of a typical walking trip (27). Because the population density of Chapel Hill is considerably lower than that of other cities, the block groups around the parks there were much larger.…”
Section: Data Collectionmentioning
confidence: 99%
“…Park neighborhoods were defined by a one-half-mile buffer around the park, about the distance of a typical walking trip (27). Because the population density of Chapel Hill is considerably lower than that of other cities, the block groups around the parks there were much larger.…”
Section: Data Collectionmentioning
confidence: 99%
“…Parking lots would be the main destination for private vehicles, which may bring congestion around. Since people would walk to their final destination, parking lots' influencing scope should be the typical walking distance, 0.25 miles (Yang & Diez-Roux, 2012), and the buffer was chosen as 500m in this paper.…”
Section: F7mentioning
confidence: 99%
“…11,12 Studies also have examined park access in specific cities by demographic characteristics such as race/ ethnicity and socioeconomic status, though these findings have been mixed, and very few studies have been national in scope. 9,10,[12][13][14][15] Some studies have shown that neighborhoods that are poor, have high unemployment, and have fewer college-educated adults have less park access. 13,15 However, other studies show neighborhoods with lower socioeconomic indicators have better access to parks and play areas.…”
mentioning
confidence: 99%